Edge-centric context sharing architecture for the internet of things : context interoperability and context-aware security - Matos, Éverton de (2020)
The adoption of the Internet of Things (IoT) in smart environments demands ad vances to cope with the large heterogeneity of IoT entities (i.e., systems, applications, and devices). Context information is an essential characteristic of these entities, which can store relevant details about their environments and related events. However, with the integration of different IoT vertical domains to provide more relevant solutions to users, providing iso lated context is no longer enough. Current context systems provide context information only locally in specific domains (i.e., vertical approaches) and not shared with other distributed entities, which is mandatory to have a horizontal and decentralized information architecture approach. Edge computing emerges as promising approach to help filling the context shar ing gap by minimizing information overhead and reducing network latency. Also, the shared context information is envisaged to be used for secure decisions and privacy-preserving. Although some context sharing approaches have been investigated by researchers, there are no efforts around the definition of an Edge-centric Context Sharing Architecture for IoT environments that mitigates the context sharing requirements and provides context aware security feature. In this sense, this work defines an edge-based system architecture able to make context sharing, which is based on an edge-to-fog approach to minimize net work overhead and latency. It also discuss the requirements for context sharing and the related work in the area. Moreover, the proposed architecture is able to provide context aware security services with the shared context information, which is considered a gap in the area.